Characterization of tumor microenvironment and cell interaction patterns in testicular and diffuse large B-cell lymphomas - Matias Autio; Oscar Brück; Marjukka Pollari; Marja-Liisa Karjalainen-Lindsberg; Klaus Beiske; Judit Mészaros Jørgensen; Harald Holte; Teijo Pellinen; Suvi-Katri Leivonen; Sirpa Leppä (Haematologica)
The tumor microenvironments (TME) of diffuse large B-cell lymphoma (DLBCL) subgroups have remained poorly characterized. Here, we dissected the composition and spatial organization of the TME in germinal center B-cell (GCB), activated B-cell (ABC), and testicular DLBCLs (T-DLBCL) using gene expression profiling and multiplex immunohistochemistry. We found that high proportions of M2-like tumor-associated macrophages (TAMs) and cytotoxic tumor-infiltrating T cells (TILs) were characteristic of ABC DLBCL TME. Furthermore, high CD8+ TIL content translated to favorable outcomes. In contrast, GCB DLBCL TME was enriched in CD4+ TILs, regulatory TILs, and a higher M1-like/M2-like TAM ratio, and high proportions of TAMs and Granzyme B+ cells associated with worse survival. TILs and TAMs interacted more frequently with M2-like TAMs and cytotoxic TILs in the ABC DLBCLs contrary to GCB subtype, where the interactions were more abundant with other TILs and CD4+ TILs. In T-DLBCL, TME resembled that of ABC DLBCL with a higher proportion of M2-like TAMs and cytotoxic cells, except that checkpoint-positive TILs were less prominent compared to DLBCL NOS. Cytotoxic TILs also interacted more with TILs and TAMs. A high amount of CD163+ TAM interactions with distinct TILs translated to unfavorable survival both in GCB DLBCL and T-DLBCL, whereas a high number of interactions between TILs and TAMs, CD4+ TILs and TAMs, and CD4+ TILs and other TILs associated with favorable outcomes only in T-DLBCL. Together, our data demonstrate biologically and clinically relevant differences in the composition of and cellular interactions in the TME between various DLBCL entities.